A New Expression for a Goda Type Breaker Index Formula in Spectral Wave Models - Zereng Chen; Qinghe Zhang; Yang Nie (Journal of Marine Science and Engineering)
The breaker index in contemporary spectral wave models is a vital parameter in studying depth-induced wave breaking, which is an important mechanism in coastal engineering. In the previous study, the authors modified a Goda type breaker index formula and parameterized it in a spectral wave model. Although this parameterization model can accurately simulate nearshore wave height variations under various laboratory and field conditions, the computation of deep-water wave conditions in the formula necessitates reverse calculation based on the incident waves, thus limiting its applicability. To solve this problem, a new expression for this Goda type breaker index is rederived, enabling its applicability to simulate breaking waves caused by variable wave conditions on open boundaries and wind field inputs in the whole computational region. The model’s capability to simulate wave heights in laboratory and field experiments is comparable to that of the original formula.